Opportunities and Challenges: Exemption from Import Duty on Imported Palestinian Products to Indonesia Post Covid-19 - Nursari, Ayu; Putri, Fadillah Dwi (Universitas Malahayati, 2024)
AbstractThis journal discusses the opportunities and challenges faced by Indonesia in exempting importduties on imported Palestinian products after the COVID-19 pandemic. The pandemic has had asignificant impact on the global economy, including international trade. Opportunities for Indonesia toexpand imports of products from Palestine are something that needs to be explored. A number ofchallenges must be overcome in implementing the import duty exemption policy. Another challenge isensuring that the import duty exemption does not harm local Indonesian producers and remains in linewith national economic development policies. This research uses the SWOT analysis method to digdeeper into the opportunities and challenges that arise in the context of exemption from import dutieson imported Palestinian products to Indonesia. It is hoped that the results of this research can contributeto further understanding of the dynamics of Indonesia's international trade, especially in relation toimported Palestinian products after the COVID-19 pandemic.